Asuhan Kebidanan Komprehensif Pada Ny. M Umur 38 Tahun Dengan PEB, CPD Dan Riwayat SC Di BPM Ny.R Wilayah Kerja Puskesmas Bumiayu Kabupaten Brebes Tahun 2023 - Irma Sarita; Himatul Khoeroh; Riyanti Riyanti (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
AKI according to WHO (2020) is 235,000 people, in Indonesia (2020) 4,627 cases, in Central Java (2020) 530 cases, in Brebes (2020) 62 cases, and AKI at Bumiayu Health Center (2020) is 2 cases. One of the efforts is to provide comprehensive midwifery care with a continuity of care approach that is carried out from pregnancy to birth control. Researchers implement comprehensive midwifery care in pregnant women, childbirth, newborns, postpartum, and family planning using Varney and SOAP documentation. The research method used was descriptive qualitative with a case study approach. Data collection used interviews, observations, physical examinations, supporting examinations, documentation studies, and literature studies, as well as medical record documentation studies. The main informant is Mrs. M with additional informants, namely 1 coordinating midwife and 1 patient's family. Based on the results of pregnancy, childbirth, newborn, postpartum, and family planning there is a problem in pregnancy, namely found PEB at 35 + 4 weeks of pregnancy with blood pressure 159 / 95 MmHg.